The Relationship between the Nine-Point Circle, the Circumscribed Circle and the Inscribed Circle of Archimedes’ Triangle - Rimcholakarn, Yuporn (Asian Health, Science and Technology Reports, 2018)
The purpose of this research was to study the relationship between the Nine-Point Circle and the Circumscribed circle of Archimedes’ triangle, and the relationship between the Nine-Point circle and the Inscribed circle of Archimedes’ triangle. The results were that the radius of the Nine-Point Circle of Archimedes’ triangle is half the radius of the Circumscribed circle of Archimedes’ triangle, and the Nine-Point circle and the Inscribed circle of Archimedes’ triangle touch internally.